2020
DOI: 10.33448/rsd-v9i3.2267
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação de processos combinados osmótico e secagem em air fryer em berinjelas condimentadas com hibisco

Abstract: 1 Aplicação de processos combinados osmótico e secagem em air fryer em berinjelas condimentadas com hibisco Application of combined osmotic and air fryer drying processes in hibiscus spiced eggplants Aplicación de procesos combinados osmóticos y secado por air fryer en berenjenas sazonadas con hibisco Resumo O presente trabalho tem como objetivo avaliar a influência da incorporação da solução obtida com hibisco, sacarose e cloreto de sódio no processo de desidratação osmótica e estudo da cinética de secagem em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Comparing the evaluated models, it can be said that the Page model was the one that best fitted the drying curve, with high R 2 and less quadratic deviation. Monteiro et al (2020) when also performing the drying kinetics of osmotically dehydrated eggplant cubes, observed that the Page model was the one with the highest determination coefficients (R 2 ) and the lowest values of the chi-square function at all temperatures analyzed. It can be seen through Figure 4, that the first 4 hours of drying were quite effective in reducing large amounts of water, then it appears that the curve reaches the most stable level of dehydration where the variation of water removed is minimal.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%
“…Comparing the evaluated models, it can be said that the Page model was the one that best fitted the drying curve, with high R 2 and less quadratic deviation. Monteiro et al (2020) when also performing the drying kinetics of osmotically dehydrated eggplant cubes, observed that the Page model was the one with the highest determination coefficients (R 2 ) and the lowest values of the chi-square function at all temperatures analyzed. It can be seen through Figure 4, that the first 4 hours of drying were quite effective in reducing large amounts of water, then it appears that the curve reaches the most stable level of dehydration where the variation of water removed is minimal.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%